Correlations between mechanical and geometrical parameters in aggregates: a tool for quality assessment and control - Xirouchakis, D. (Bulletin of the Geological Society of Greece, 2013)
Correlations between mechanical and geometrical parameters in aggregates can be used as quality and performance prediction tools. I evaluated the following parameter pairs: dry and wet resistance to wear (MDE & MDS), and resistance to fragmentation (LA); polishing resistance and abrasion (PSV–AAV); and flakiness and shape index (FI–SI). The data set comprises slags, sedimentary, igneous, and metamorphic rocks tested according to EN standard test methods. FI and SI are positively correlated (r = 0.83) and can be well described by the 1:1 line. Wet and dry resistance to wear are strongly correlated (r = 0.98) with MDE ≈ 2·MDS. Dry resistance to fragmentation (LA) and wet resistance to wear (MDE) are well correlated (r = 0.81), and can be described with the equation LA = 4.95×MDE 0,61 (R2 = 0.69). According to the PSV–AAV correlation, aggregates are divided into two groups with contrasting behavior. Limestones and slags (r = −0.49 to −0.69) exhibit high polishing for high abrasion resistance (high PSV–low AAV), whereas sandstones and mafic to intermediate volcanics (r = 0.44 to 0.39) exhibit high polishing for low abrasion resistance (high PSV–high AAV). Peridotites belong to either PSV–AAV group depending on the soft minerals.